Labor Divides, Informality, and Regulation: The Public Opinion on Labor Law in Latin America. Issue 1 (April 2019) - Berens, Sarah; Kemmerling, Achim
While scholarship on the politics of labor market divides and labor law in Latin America has bloomed in recent years, this literature rarely looks at the role of public opinion. Using data on public attitudes towards labor law for 18 Latin American countries, we start filling this gap. We follow the literature on labor market divides to see how far those at the margins of the formal labor market differ in their opinions from the formally employed. We find that large segments of the people perceive labor law as protective for workers, but there are also important divides: Whereas formal sector workers indeed assess the protective function of labor law positively, informal sector workers are more sceptical. Moreover, we find feedback effects of labor law on these differences of opinion. We conclude with a discussion how these divides in attitudes also have political effects, especially on voting behavior.